2016
DOI: 10.1080/00325481.2016.1181412
|View full text |Cite
|
Sign up to set email alerts
|

Proactive and Progressive Approaches in Managing Obesity

Abstract: Despite the advice clinicians have been giving patients about the importance of restricting their food intake and increasing physical activity levels, the Centers for Disease Control and Prevention (CDC) states that 78.6 million adults in the United States (US) are still obese. With these statistics in mind, this symposium provided insights on the genetic, cultural, and environmental underpinning of obesity and discussed the latest research on pharmacotherapy, surgery, and the need to individualize treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…To date, the mechanism of how and why an imbalance occurs has not been fully understood. The regulation of energy homeostasis is complex and involves multiple factors, such as neural and endocrine systems related to food intake, environments linked to food availability, and sedentary lifestyles associated with energy expenditure [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the mechanism of how and why an imbalance occurs has not been fully understood. The regulation of energy homeostasis is complex and involves multiple factors, such as neural and endocrine systems related to food intake, environments linked to food availability, and sedentary lifestyles associated with energy expenditure [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a Finnish study that have shown that those who succeed with weight maintenance are less sedentary, are more physically active (one hour per day), consume less alcohol and smoked less [5]. Addressing these issues requires behaviour and lifestyle modifications and the provision of individualised therapy [6].…”
Section: Introductionmentioning
confidence: 99%